Pearls & Oy-sters: Sequential Bilateral Hearing and Vision Loss With Optic Disc Swelling Due to Sphenoid Bone Craniofacial Fibrous Dysplasia. (28th February 2023) - Handley, Joel D.; Mathur, Sachin; Chhetri, Suresh K.
Abstract : Bilateral optic disc swelling is a common finding but rarely associated with multiple cranial neuropathies. In this case, an 18-year-old man presented with subacute sequential hearing loss followed by subacute sequential visual loss. Clinical examination revealed bilateral optic disc swelling. Lumbar puncture revealed a normal opening pressure of 15 cmH2 o. This case discusses a rare but important cause of bilateral optic disc swelling in the context of hearing loss, disequilibrium, and a normal CSF opening pressure. An overview of the literature is provided, and treatment options are discussed to guide further management of similar cases.